Pediatric chronic nonbacterial osteomyelitis of the mandible: Seattle Children's hospital 22-patient experience - Austin Gaal; Matthew L. Basiaga; Yongdong Zhao; Mark Egbert (BMC, 2020)
Abstract Background Studies evaluating treatment responses for chronic nonbacterial osteomyelitis (CNO) are lacking. We aimed to measure and compare response rates of medical treatments, time to response of medical treatments among patients with CNO of the mandible, and describe bacterial contamination rates from biopsy. Methods We conducted a retrospective chart review of all patients diagnosed with CNO of mandible between 2003 and 2017 and extracted demographic, clinical, laboratory, imaging and surgical data. Detailed medication use and response to medications were recorded. The primary outcome was response to medical treatments defined as improvement of presenting symptoms, inflammatory markers, and imaging if available. Medical treatments included nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, disease modifying anti rheumatic drugs (DMARDs), anti-tumor necrosis factor (TNF) therapy, and pamidronate. Descriptive analysis was performed when appropriate. Multivariable logistic regression and Kaplan-Meier curves were applied to compare the responses to medical treatments and time to full response. Results We identified 22 patients with a median age of 11 and 36% were female. Four patients (18%) had multifocal bone lesions. CT findings (n = 21) showed lytic lesions (62%) and sclerosis (90%). MRI (n = 14) revealed hyperintensity within bone marrow (100%), soft tissue (71%) and bony expansion (71%). Non-antibiotic treatments including NSAIDs (n = 18), glucocorticoids (n = 10), DMARDs (n = 9), anti-TNF therapy (n = 5) and pamidronate (n = 6) were applied. Rates of full responses to anti-TNF therapy (60%) and pamidronate (67%) were higher than that to NSAIDs (11%) (p < 0.05). Patients receiving pamidronate responded more rapidly than those receiving anti-TNF therapy (median two vs 17 months, p = 0.01) when there was a full response. All had bone biopsies. Intraoral biopsy was performed in 12 of 13 operated in our center and the most common contaminants were Neisseria spp and Streptococcus viridians. Conclusion Both anti-TNF and pamidronate appeared superior to NSAIDs alone in treating mandibular CNO. Patients receiving pamidronate responded faster than those receiving anti-TNF therapy.